Effectiveness of Lyubomirsky’s Happiness Training on Life Satisfaction and Hope in Mothers of Children with Autism Spectrum Disorder - Mahjoor, Fatemeh; Fazeli Mehrabadi, Alireza (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to evaluate the effectiveness of Lyubomirsky’s happiness training package on life satisfaction and hope in mothers of children diagnosed with autism spectrum disorder (ASD).Methods and Materials: The research employed a quasi-experimental design with pretest-posttest and a control group. A total of 40 mothers of children with ASD from the Golhaye Beheshti Center in Qom were selected through simple random sampling and randomly assigned to experimental and control groups (20 participants each). After accounting for attrition, the final sample included 15 participants per group. The intervention group received Lyubomirsky’s happiness training over eight 90-minute sessions, while the control group received no intervention. Data were collected using the Satisfaction with Life Scale (Diener et al., 1985) and the Hope Scale (Snyder et al., 1991), both validated for use in Iranian samples. Inferential analysis was conducted using ANCOVA in SPSS version 26.Findings: Results showed that, after controlling for pretest scores, there was a significant increase in posttest life satisfaction scores in the intervention group compared to the control group (F(1,33) = 13.437, p = .001, η² = .289). Similarly, hope scores significantly increased in the intervention group (F(1,33) = 18.268, p < .001, η² = .356). Significant improvements were also observed in the subscales of agency thinking (F(1,33) = 12.000, p = .001, η² = .267) and pathways thinking (F(1,33) = 5.621, p = .024, η² = .146). All assumptions for ANCOVA, including normality, homogeneity of regression slopes, and linearity, were met.Conclusion: Lyubomirsky’s happiness training proved to be an effective positive psychology intervention in enhancing life satisfaction and hope among mothers of children with ASD. Given its structured, culturally adaptable, and non-pharmacological nature, it can be implemented in family counseling and rehabilitation settings to promote psychological well-being in this high-risk population.